PATRIOTIC EDUCATION OF STUDENTS IN TEACHING PSYCHOLOGICAL AND PEDAGOGICAL DISCIPLINE (ON EXAMPLE OF CRITICAL THINKING TECHNOLOGY) - Valeriy Budak; Oksana Oleksiuk (Borys Grinchenko Kyiv Metropolitan University, 2019)
The article deals with the problem of formation of university students during the teaching of the psychological and pedagogical disciplines not only the qualities of the patriot of their country, but also the formation of a person who must meet the requirements for the personality of the patriot leader. Examples of «Leader - Thought Thinking», «Synkveyn», «Press» methods during the teaching of psychological and pedagogical disciplines are given. The analysis of the students' tasks implementation of the «Press» method is conducted in accordance with the determined components of the process of patriotic education: cognitive, motivational-value, activity-behavioural, personally-estimated and socially-valued. The following analysis of the essential characteristic of student answers is outlined as a challenge for further scientific developments.